Yard Bay Allocation Method for Twin 40ft Container Terminal-Oriented - Daofang Chang; Youfang Huang; Wei Yan; Yu Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The efficiency of container handling has got greatimprovement with the usage of the 40ft quay crane and the twin 40ft yardcrane.Reasonable bay planning strategies is necessary to reach the high handing efficiency by the twin 40ft yard crane. This paper studies both bay planning and row planning for yard bay allocation. The models of bay planning and row planning are created, and the discrete particle swarm optimization algorithm is used to obtain the optimum solution of the models. Finally, the numerical experiments show that the proposed approach can solve the yard bay allocation effectively. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3428